Participation in forest management practices, livelihood diversification and welfare of forest dwellers in Gambari Forest Reserve, Oyo State, Nigeria (2021)
The management of forests, a source of livelihood in Nigeria, especially in the rural areas has received little attention in recent times. As a result, most of the forest dwellers who depend on these forests for survival are poor and are beginning to diversify their livelihood into off and non-forest activities as a relevant source of income. This study assessed participation in forest management practices, livelihood diversification and, the welfare of forest dwellers in Gambari Forest Reserve, Oyo State, Nigeria. Primary data, collected from 121 respondents using a multistage sampling Procedure were analyzed employing Descriptive Statistics, Logit, Tobit, and Ordinary Least Squares model. The decision to participate in forest management practices was significantly linked to gender, age, and membership in a forest association. Also, participation in forest management practices, gender, age, and credit accessibility significantly influenced livelihood diversification positively while farm size and monthly income had negative effects. The welfare of forest dwellers was found to be positively influenced by being a married indigene, having access to credit, participation in forest management practices, livelihood diversification, and monthly income while age, education, and market distance from homestead negatively affected the welfare of forest dwellers